Lung-protective ventilation initiated in the emergency department (LOV-ED): a study protocol for a quasi-experimental, before-after trial aimed at reducing pulmonary complications. Issue 4 (11th April 2016) - Fuller, Brian M; Ferguson, Ian; Mohr, Nicholas M; Stephens, Robert J; Briscoe, Cristopher C; Kolomiets, Angelina A; Hotchkiss, Richard S; Kollef, Marin H
Abstract : Introduction: In critically ill patients, acute respiratory distress syndrome (ARDS) and ventilator-associated conditions (VACs) are associated with increased mortality, survivor morbidity and healthcare resource utilisation. Studies conclusively demonstrate that initial ventilator settings in patients with ARDS, and at risk for it, impact outcome. No studies have been conducted in the emergency department (ED) to determine if lung-protective ventilation in patients at risk for ARDS can reduce its incidence. Since the ED is the entry point to the intensive care unit for hundreds of thousands of mechanically ventilated patients annually in the USA, this represents a knowledge gap in this arena. A lung-protective ventilation strategy was instituted in our ED in 2014. It aims to address the parameters in need of quality improvement, as demonstrated by our previous research: (1) prevention of volutrauma; (2) appropriate positive end-expiratory pressure setting; (3) prevention of hyperoxia; and (4) aspiration precautions. Methods and analysis: The lung-protective ventilation initiated in the emergency department (LOV-ED) trial is a single-centre, quasi-experimental before-after study testing the hypothesis that lung-protective ventilation, initiated in the ED, is associated with reduced pulmonary complications. An intervention cohort of 513 mechanically ventilated adult ED patients will be compared with over 1000 preintervention control patients. The primary outcome is a composite outcome of pulmonary complications after admission (ARDS and VACs). Multivariable logistic regression with propensity score adjustment will test the hypothesis that ED lung-protective ventilation decreases the incidence of pulmonary complications. Ethics and dissemination: Approval of the study was obtained prior to data collection on the first patient. As the study is a before-after observational study, examining the effect of treatment changes over time, it is being conducted with waiver of informed consent. This work will be disseminated by publication of full-length manuscripts, presentation in abstract form at major scientific meetings and data sharing with other investigators through academically established means. Trial registration number: NCT02543554.